(untitled) (CIPEEX, 2025)
INTRODUCTION: Prenatal care consists of the assistance of the health team during a woman’s pregnancy to promote maternal and fetal health, in order to prevent, identify and treat possible complications during the gestational period. In order to assist in prenatal care, devices such as blood pressure monitors, temperature, heart rate, respiratory rate and electrodes to monitor uterine contractions, present themselves as allies of obstetric medicine, assisting in the early detection of complications and prevention of complications. In this sense, the use of telemedicine and its technologies in the field of obstetrics represents an instrument of fundamental importance in prenatal monitoring when providing remote medical care through digital means. OBJECTIVE: To analyze the impact of telemedicine during the prenatal period. METHODOLOGY: This is an integrative review of the literature of studies collected in the databases: "PubMed" "LILACS" and "Scielo", using the Descriptors in Health Sciences (DeCS): "Pregnancy" "Prenatal" and "Telemonitoring". 5 studies were included, in English and Portuguese, carried out between 2016 and 2022. Articles that did not address the topic and that did not respond to the proposed objective were excluded. RESULTS: It was evidenced that obstetric telemonitoring can be applied as a way to contribute to medical care in various contexts during pregnancy. From this, it was observed that the prevalence of premature births was 8.34% in monitored pregnant women and 10.18% in those not monitored during the gestational period. In addition, in relation to the number of monitorings, women who did not receive any monitoring during pregnancy had a proportion of premature births of 20.56%, women who had between 1-3 monitorings had a rate of 9.81%, while in the category of 4-6 monitorings there was a percentage of 5.9% and only 3.23% In women who performed 7 or more monitorings during pregnancy. CONCLUSION: It can be said that telemedicine, together with the support of advanced technologies and the care strategies adopted, contributes to favorable results in the development of pregnancy, thus promoting a healthy pregnancy.